Geografija in celostni razvoj podeželja - Pelc, Stanko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
We write about the position of rural geography within Slovene geography and its possible application in the process of integrated rural development. We draw our conclusions on the basis of the presence of rural geography as a course in study programmes in Slovenian and some foreign Universities, the amount of bibliographical units from the field of rural geography in the central geographical library of Slovenia and our experiences with the project of integrated rural development and the village renovation in Slovenia.
Keywords: družbena geografija; human geography; podeželje; regionalni razvoj; rural area; Slovenia; Slovenija; sustainable development; trajnostni razvoj